Wester Ross - Ballantyne, Colin K.; Bradwell, Tom (Springer Science and Business Media B.V., 2021)
Wester Ross is an area of striking geodiversity, containing some of the most impressive glacial and postglacial landforms in Scotland. The region is bisected by the Moine Thrust Zone, west of which a platform of Archaean gneiss supports Torridonian sandstone mountains, and east of which the geology is dominated by metasedimentary rocks of the Moine Supergroup. Successive episodes of Pleistocene glaciation have resulted in the formation of glacial troughs that continue westward as fjords, and some of the most dramatic cirques in Scotland. The last ice sheet flowed across the area in a northwesterly direction, feeding a large ice stream in the trough between mainland Scotland and the Outer Hebrides. During its retreat, the ice front deposited a nested sequence of submarine recessional moraines in fjords and a chain of terrestrial moraines representing a late-stage (~15.3 ka) readvance of the retreating ice-sheet margin. During the Loch Lomond (≈ Younger Dryas) Stade of ~12.9 to 11.7 ka, Wester Ross was partly reoccupied by an icefield centred near the present drainage divide and supported numerous independent cirque and valley glaciers that deposited prominent terminal, lateral and recessional moraines. After deglaciation, the landscape was modified by rock-slope failures, frost action, solifluction and aeolian activity, whilst glacio-isostatic uplift resulted in the formation of raised marine shorelines of both Lateglacial and Holocene age.